Genome-wide comparative and evolutionary analysis of Calmodulin-binding Transcription Activator (CAMTA) family in Gossypium species - Pant, Poonam (Sci Rep, 2018)
The CAMTA gene family is crucial in managing both biotic and abiotic stresses in plants. Our comprehensive analysis of this gene family in cotton resulted in the identification of 6, 7 and 9 CAMTAs in three sequenced cotton species, i.e., Gossypium arboreum, Gossypium raimondii, and Gossypium hirsutum, respectively. All cotton CAMTAs were localized in the nucleus and possessed calmodulin-binding domain (CaMBD) as identified computationally. Phylogenetically four significant groups of cotton CAMTAs were identified out of which, Group II CAMTAs experienced higher evolutionary pressure, leading to a faster evolution in diploid cotton. The expansion of cotton CAMTAs in the genome was mainly due to segmental duplication. Purifying selection played a significant role in the evolution of cotton CAMTAs. Expression profiles of GhCAMTAs revealed that GhCAMTA2A.2 and GhCAMTA7A express profoundly in different stages of cotton fiber development. Positive correlation between expression of these two CAMTAs and fiber strength confirmed their functional relevance in fiber development. The promoter region of co-expressing genes network of GhCAMTA2A.2 and GhCAMTA7A showed a higher frequency of occurrence of CAMTA binding motifs. Our present study thus contributes to broad probing into the structure and probable function of CAMTA genes in Gossypium species.